Analysis of the relationship between management and service quality in Tembi Tourism Village - Dimas Budi Prakoso; Farrel Ahmad Jayyidi (Journal of Rural Tourism, 2024)
Purpose - The purpose of this study is to analyze the impact of management unification on service quality and visitor satisfaction in Tembi Tourism Village, with a focus on improving hospitality services in rural tourism. Methodology/Design/Approach - A mixed-methods approach (qualitative and quantitative) was used. The study combined surveys and descriptive analysis to understand the effects of management unification on service quality and visitor satisfaction. Data were collected via an online survey using Google Forms, targeting tourists visiting Tembi Tourism Village.Finding - The study found that management unification significantly improved service quality and visitor satisfaction at Tembi Tourism Village. This led to an increase in tourist visits, suggesting that effective management coordination positively affects both service delivery and the overall tourist experience. Originality/Value - This research highlights the importance of management unification in enhancing service quality and visitor satisfaction, particularly in rural tourism settings. The findings provide practical recommendations, such as regular evaluations and innovative policy implementations, to support continued growth and increased tourism visits to the destination.